UPAYA PENINGKATAN HASIL BELAJAR BOLA VOLI MINI MELALUI PERMAINAN BONAS PADA SISWA KELAS IV SDN 02 BONDANSARI WIRADESA TAHUN PELAJARAN 2013/2014 (Department of Physical Education, Sport, Health and Recreation, 2015)
This study aims to improve learning outcomes through audiovisual media handstand posture and consistency for high school students in the learning of Physical Education , Sport and Health . This study uses action research . In the implementation of the first cycle and second cycle meetings held 1 meeting . The subjects were a class XI Science SMAN 1 Sukorejo , District Sukorejo , Kendal . The instruments used in the data collection was obtained from observations at the time of learning , performance test and written test students . Based on the results obtained in the first cycle of learning outcomes that can meet the KKM as much as 31.4 % of the total number of students in the second cycle and increased to 82.9 % of the total number of students . Based on the above results , it can be concluded that the application of audiovisual media and consistency posture can improve learning outcomes handstand in class XI Science SMAN 1 Sukorejo . Expected for the Physical Education teacher at SMA N 1 Sukorejo to use audiovisual media and consistency in learning handstand posture .